Tolstoy's Family Prototypes in War and Peace - Cooke, Brett (Evolution, cognition, and the arts., 2020)
Did affection for members of his family influence Tolstoy's characterizations in War and Peace? Comparison of the novel with the writer's family history reveals preferential treatment of those with greater relatedness to him--excluding his autoportraits. It also explains many narrative gaps and curious devices, including coincidences, ""fate, "" and incest